Growth and Yield of Rice (Oryza sativa L.) Under Raised- and Sunken-Bed System as Affected by Saline Irrigation in Baros, Bantul, Yogyakarta - Nafi'atul Muflikhah; Budiastuti Kurniasih; Tohari Tohari (Jurnal Ilmu Pertanian, 2018)
It is expected that by utilizing marginal land (e.g. saline field) is able to increase rice production under saline condition. One of integrated approaches that can be applied is a raised- and sunken-bed system. This experiment aimed to investigate the growth and yield of rice under raised- and sunken-bed system as affected by saline irrigation. The field experiment was conducted at Baros Helmet, Bantul District, Yogyakarta from October 2016 to February 2017. The experiment was arranged in a multi-location (oversite) design, consisted of saline irrigation (S1) and nonsaline irrigation (S0) in a raised-bed (A1) and sunken-bed (A0) planting system. The observations were done on leaf area index, chlorophyll a, chlorophyll b, total chlorophyll, photosynthesis rate, total dry weight, root length, leaf Na+ and K+ concentration, proline concentration, maturity and dry grain yield (DGY). The results showed that saline irrigation negatively affected leaf area index, photosynthetic rate and root length of rice grown at sunken-bed. However, leaf Na+ concentration and leaf proline concentrations of rice grown at sunken-bed were higher. The leaf K+ concentration decreased with increasing Na+ concentration. Although saline irrigation could accelerate harvesting age of rice grown at sunken-bed, the dry grain yield of rice grown at sunken-bed did not significantly different with that of rice grown at raised-bed.